Fairness perceptions regarding in-work benefits: a survey experiment - Senghaas, Monika; Osiander, Christopher; Stephan, Gesine; Struck, Olaf (International journal of sociology and social policy, 2022)
PurposeIn many countries, individuals can receive welfare support whilst simultaneously being employed. The level of earned income that welfare recipients are allowed to keep has long been a subject of debate. Core issues include whether in-work benefit regulations provide incentives for individuals to expand labour market participation and are thus also socially effective and whether the population perceives welfare benefits for individuals who earn own income as fair. This article contributes to the debate about the social legitimacy of in-work benefit regulations by shedding light on the principles guiding judgements about an adequate amount of in-work benefit receipt.Design/methodology/approachThe authors use a factorial survey experiment to investigate which factors guide judgements about an adequate level of in-work benefit receipt. In the authors' factorial survey, the household composition, health status, and monthly earnings of a hypothetical in-work benefit recipient were varied experimentally. The study investigates Germany's basic income support programme, a means-tested social policy programme that targets both unemployed and employed individuals.FindingsThe results show that respondents consider higher earnings retention rates for lower-income earners to be fair. This preference mirrors the German legislation, which is based on the principle of need. Furthermore, the presence of children and of physical as well as mental health impairments are associated with support for higher earnings retention rates.Originality/valueThe findings suggest that citizens support the core features of in-work benefit regulations but do not consider in-work benefit recipients as a homogenous group when assessing the adequate level of benefit receipt.